Diffuseness of coronary artery disease impacts on immediate hemodynamic and predicted clinical outcomes - Shigetaka Kageyama; Pruthvi Chenniganahosahalli Revaiah; Tsai Tsung-Ying; Kotaro Miyashita; Akihiro Tobe; Neil O’Leary; Johan H. C. Reiber; Shengxian Tu; Azfar Zaman; Manel Sabaté; Helge Möllmann; Faisal Sharif; et al. (Scientific Reports)
Abstract Diffuse coronary artery disease (CAD) impacts the immediate hemodynamic and clinical outcomes of percutaneous coronary intervention (PCI). We evaluated whether the diffuse pattern of CAD derived from angiographic Quantitative flow ratio (QFR) impacts the immediate hemodynamic outcome post-PCI and the medium term predicted vessel-oriented composite endpoint (VOCE). Paired pre-procedure QFRs were assessed in 503 patients and 1022 vessels in the Multivessel TALENT (MVT) trial. The pathophysiological pattern of CAD was defined as “predominantly diffuse” or “focal” according to a virtual QFR pullback pressure gradient (PPG) index < 0.78 and ≥ 0.78, respectively. Physiological “focal severity” was assessed using the QFR gradient per mm (dQFR/ds), with a value ≥ 0.025/mm the threshold for a “major gradient”. A post-PCI QFR ≥ 0.91 was considered optimal. Median pre-PCI PPG index was 0.70 (IQR 0.59–0.80). The prevalence of “predominantly diffuse” CAD and “major gradient” were 68.6% and 85.8%, respectively. A “Predominantly diffuse” pattern with a major gradient had a higher risk of a post-PCI QFR < 0.91 (OR 1.52,95%CI 1.47–1.58). In multivariable analysis, low QFR PPG index (diffuse disease) was an independent determinant of a post-PCI QFR < 0.91 (per 0.1 decrease of QFR PPG index, OR:9.8, 95% CI 3.0–32.2, p < 0.001). Based on post-PCI QFR the predicted 2-year VOCE, a powered endpoint in the MVT trial, was 6.1% and 4.2% in diffuse and focal lesions, respectively. A pre-procedure physiological pattern of diffuse CAD is an independent determinant of an unfavourable immediate hemodynamic outcome post-PCI, and detrimentally affects the predicted 2-year VOCE. Clinical Trial Registration URL: https://www.clinicaltrials.gov/ct2/show/NCT04390672 Unique Identifier: NCT04390672 (registration date 15/05/2020)